Understanding institutional diversity - Ostrom, Elinor 1933-2012 (Princeton Univ. Press, 2005)
The analysis of how institutions are formed, how they operate and change, and how they influence behavior in society has become a major subject of inquiry in politics, sociology, and economics. A leader in applying game theory to the understanding of institutional analysis, Elinor Ostrom provides in this book a coherent method for undertaking the analysis of diverse economic, political, and social institutions.Understanding Institutional Diversity explains the Institutional Analysis and Development (IAD) framework, which enables a scholar to choose the most relevant level of interaction for a particular question. This framework examines the arena within which interactions occur, the rules employed by participants to order relationships, the attributes of a biophysical world that structures and is structured by interactions, and the attributes of a community in which a particular arena is placed.The book explains and illustrates how to use the IAD in the context of both field and experimental studies. Concentrating primarily on the rules aspect of the IAD framework, it provides empirical evidence about the diversity of rules, the calculation process used by participants in changing rules, and the design principles that characterize robust, self-organized resource governance institutions